2020
DOI: 10.1016/j.tetlet.2020.151798
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of antipyrine and haloantipyrines in Pd-catalyzed C H bond arylations

Abstract: We reported herein the Pd-catalyzed direct arylation of antipyrine using Pd(OAc) 2 as catalyst associated with KOAc as inexpensive base. In most cases, diethyl carbonate was used a sustainable solvent. The reaction tolerated a wide range of functional groups on the aryl bromide partners (e.g., nitrile, nitro, chloro, fluoro, formyl, acetyl, propionyl, benzoyl, ester, methyl, methoxy). In addition, some nitrogen-containing heteroaryl bromides were also efficiently coupled with antipyrine. We also demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The literature data analysis has shown that antipyrine and its non-uorinated analogs readily undergo the Pd-catalyzed direct arylation with the different arylhalogenides. 46,47 However, our numerous efforts to involve 5-triuoromethyl-antipyrine 1a into the direct arylation with arylhalogenides were ineffective, despite the use of various palladium catalysts {Pd(OAc) 2 , Pd 2 (dba) 3 }, bases (AcOK, K 2 CO 3 , Cs 2 CO 3 , K 3 PO 4 ), ligands (ligand-free, XPhos), solvents (CO(OEt) 2 , EtOH-H 2 O, DMA, toluene, 1,4-dioxane), temperature modes (100-160 C) and ratios of reagents in these reactions. The extended experiments are presented in Table S1 (please see, ESI †).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature data analysis has shown that antipyrine and its non-uorinated analogs readily undergo the Pd-catalyzed direct arylation with the different arylhalogenides. 46,47 However, our numerous efforts to involve 5-triuoromethyl-antipyrine 1a into the direct arylation with arylhalogenides were ineffective, despite the use of various palladium catalysts {Pd(OAc) 2 , Pd 2 (dba) 3 }, bases (AcOK, K 2 CO 3 , Cs 2 CO 3 , K 3 PO 4 ), ligands (ligand-free, XPhos), solvents (CO(OEt) 2 , EtOH-H 2 O, DMA, toluene, 1,4-dioxane), temperature modes (100-160 C) and ratios of reagents in these reactions. The extended experiments are presented in Table S1 (please see, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…56 It explains the weak reactivity of compound 1a in the reactions of electrophile arylation comparing to the non-uorinated antipyrine in analogous transformations. 46,47 Then, we investigated the possibility of modifying polyuoroalkyl-antipyrines 1 at the center C4 in the Pdcatalyzed Suzuki and Sonogashira cross-coupling reactions. At rst, 4-bromo-5-polyuoroalkyl-antipyrines 4a-d and 4-iodo-5-polyuoroalkyl-antipyrines 5a, b were synthesized by the treatment of the initial heterocycles 1a-d with N-bromo-or N-iodosuccinimide (NXS) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, the direct C–H functionalization reactions featured with atom- and step-economy have become important tools for modifying organic compounds . Until now, there were some examples about direct C–H functionalization of pyrazolones including arylation, alkenylation, alkynylation, acylation, and thiolation . However, these methods had some disadvantages, such as using precious metals or unavailable starting materials, utilizing strong oxidant, and needing complex reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Owing to their intriguing profiles and prominent applications in various fields, considerable attention has been directed towards the synthesis and functionalization of pyrazolone compounds. [8][9][10][11][12][13][14][15][16][17][18][19] In recent years, some previous works have reported the halogenation of pyrazolones via oxidative C-X bond formation (Scheme 1b). In 2018, Lamar 20 reported a visible light photoredox bromination of antipyrine using N-bromosuccinimide (NBS) as the halogen source.…”
mentioning
confidence: 99%